On implementing relational databases on DNA strands - Katsányi, István (Acta Cybernetica, 2003)
This work describes the theoretical bases of the implementation of relational databases in test tubes, using an abstract model of molecular computing. It specifies the representation of relations and the execution program of the relational algebra (RA) operations. We investigate the possibilities of practical usage of the proposed model as well as the bounds of it.